Valuasi ekonomik museum Benteng Vredeburg di Yogyakarta :: Travel cost method - ALEXANDRA, Happy Orylia ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Museum Benteng Vredeburg is famous national museum in Yogyakarta but the visitors still be low. This study is aim to applying one of method of appraisal that is Travel Cost Method (TCM). This purpose of research is to determine factors that influence the visits and also estimate the worth of Museum Benteng Vredeburg. Variable which applied in this research is level of visit as dependent variables, while the independent variable is travel cost, income, age, quality dummy, and substitution dummy. This research use a sample number of 100 visitors Museum Benteng Vredeburg. The research indicates that travel cost, earnings, age, and quality of place influence the amount of individuals visit. The Museum Benteng Vredeburg value per year stay at intervals between Rp216.208.472.097 and Rp467.226.249.260 with consumers surplus equal to Rp3.062.110,31 per year or equal to Rp1.354.916,07 per individuals every visits.